The Fanconi Anemia Pathway Protects Genome Integrity from R-loops. - María L García-Rubio; Carmen Pérez-Calero; Sonia I Barroso; Emanuela Tumini; Emilia Herrera-Moyano; Iván V Rosado; Andrés Aguilera (PLoS Genetics)
Co-transcriptional RNA-DNA hybrids (R loops) cause genome instability. To prevent harmful R loop accumulation, cells have evolved specific eukaryotic factors, one being the BRCA2 double-strand break repair protein. As BRCA2 also protects stalled replication forks and is the FANCD1 member of the Fanconi Anemia (FA) pathway, we investigated the FA role in R loop-dependent genome instability. Using human and murine cells defective in FANCD2 or FANCA and primary bone marrow cells from FANCD2 deficient mice, we show that the FA pathway removes R loops, and that many DNA breaks accumulated in FA cells are R loop-dependent. Importantly, FANCD2 foci in untreated and MMC-treated cells are largely R loop dependent, suggesting that the FA functions at R loop-containing sites. We conclude that co-transcriptional R loops and R loop-mediated DNA damage greatly contribute to genome instability and that one major function of the FA pathway is to protect cells from R loops.